Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Evaluating past and future contributions of conservation programs to species recovery - Rebeca E. Young; H. Resit Akçakaya; Elizabeth L. Bennett; Michael Hoffmann; Michael A. Hudson; Barney Long; Thalassa McMurdo Hamilton; Kelsey Neam; Megan A. Owen; Richard P. Young; Molly K. Grace (Conservation Biology, 2026)
Impact evaluation of conservation actions is a crucial step in global efforts to curb the biodiversity crisis. Through robust impact evaluation, practitioners can assess the effectiveness of conservation strategies and optimize the use of limited resources. Despite a proliferation of methods and tools for evaluating conservation impact, no standardized method exists to assess and compare the impact, and global contribution, of species recovery programs. To address this gap, we devised an evaluation framework, based on the International Union for Conservation of Nature (IUCN) Green Status of Species (GSS), a global standard for measuring species recovery. We sought to provide a way for conservation program delivery partners to evaluate the effectiveness of their programs in contributing to global species recovery. We adapted 2 scenarios used in GSS assessments to estimate the impact of worldwide conservation actions on a species (the counterfactual current scenario and the future without conservation scenario), in order to propose a new assessment: the program GSS, a method allowing conservation practitioners to estimate the past and potential future impacts of a conservation program relative to the global impact. To identify the strengths and limitations of applying the GSS method at the program level and to gather proof of concept for our adaptation, we tested the proposed method on 16 species recovery programs. The program GSS approach identified past or future impacts of program actions on species status in 9 of the programs assessed. The detectability of program impact and the relative impact of the program compared with global impact were influenced by time since program establishment and program scope (i.e., proportion of a species’ population or distribution included in the program). Our framework for program GSS assessments can provide practitioners with a standard, straightforward, and cost‐effective way to communicate conservation successes and expected future impacts. Results from our program GSS framework can be compared with the global recovery of a species (conservation legacy and conservation impact) and thus indicate a program's contribution to the recovery of the entire species.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

What is ‘good evidence’ for environmental decision making? Insights from professionals working at the science-policy interface - Elizabeth A. Nyboer; Andrew N. Kadykalo; Nathan Young; Vivian M. Nguyen; Trina Rytwinski; John-Francis Lane; Joseph R. Bennett; Nathan Harron; Susan M. Aitken; Graeme Auld; David Browne; Aerin L. Jacob; et al. (Environmental Science & Policy, 2025)

Accelerating biotherapeutics discovery: Blueprint for a universal LC-MALDI-MS offline approach - Elizabeth F. Bayne; Xiong-Zhuo Gao; Yuan Jiang; Raffeal Bennett; Erik L. Regalado; Gregory F. Pirrone; Alexey A. Makarov (Analytica Chimica Acta, 2025)

Putting numbers to a metaphor: A Bayesian Belief Network with which to infer Soil Quality and Health - Kirsty L. Hassall; Joanna Zawadzka; Alice E. Milne; Ronald Corstanje; James A. Harris; A. Gordon Dailey; Aidan M. Keith; Margaret J. Glendining; S.P. McGrath; Lindsay C. Todman; Paul Alexander; Philippa Arnold; et al. (European Journal of Agronomy, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

On-orbit calibration and performance of the EMIT imaging spectrometer - David R. Thompson; Robert O. Green; Christine Bradley; Philip G. Brodrick; Natalie Mahowald; Eyal Ben Dor; Matthew Bennett; Michael Bernas; Nimrod Carmon; K. Dana Chadwick; Roger N. Clark; Red Willow Coleman; et al. (Remote Sensing of Environment, 2024)

The ten steps to responsible Inland fisheries in practice: reflections from diverse regional case studies around the globe - Steven J. Cooke; Elizabeth Nyboer; Abigail Bennett; Abigail J. Lynch; Dana M. Infante; Ian G. Cowx; T. Douglas Beard; Devin Bartley; Craig P. Paukert; Andrea J. Reid; Simon Funge-Smith; Edith Gondwe; et al. (Reviews in Fish Biology and Fisheries, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Altered structure of bat–prey interaction networks in logged tropical forests revealed by metabarcoding - David R. Hemprich‐Bennett; Victoria A. Kemp; Joshua Blackman; Matthew J. Struebig; Owen T. Lewis; Stephen J. Rossiter; Elizabeth L. Clare (Molecular Ecology, 2021)
Habitat degradation is pervasive across the tropics and is particularly acute in Southeast Asia, with major implications for biodiversity. Much research has addressed the impact of degradation on species diversity; however, little is known about how ecological interactions are altered, including those that constitute important ecosystem functions such as consumption of herbivores. To examine how rainforest degradation alters trophic interaction networks, we applied DNA metabarcoding to construct interaction networks linking forest‐dwelling insectivorous bat species and their prey, comparing old‐growth forest and forest degraded by logging in Sabah, Borneo. Individual bats in logged rainforest consumed a lower richness of prey than those in old‐growth forest. As a result, interaction networks in logged forests had a less nested structure. These network structures were associated with reduced network redundancy and thus increased vulnerability to perturbations in logged forests. Our results show how ecological interactions change between old‐growth and logged forests, with potentially negative implications for ecosystem function and network stability.

Conservation resource allocation, small population resiliency, and the fallacy of conservation triage - David A. Wiedenfeld; Allison C. Alberts; Ariadne Angulo; Elizabeth L. Bennett; Onnie Byers; Topiltzin Contreras‐MacBeath; Gláucia Drummond; Gustavo A. B. da Fonseca; Claude Gascon; Ian Harrison; Nicolas Heard; Axel Hochkirch; et al. (Conservation Biology, 2021)
Some conservation prioritization methods are based on the assumption that conservation needs overwhelm current resources and not all species can be conserved; therefore, a conservation triage scheme (i.e., when the system is overwhelmed, species should be divided into three groups based on likelihood of survival, and efforts should be focused on those species in the group with the best survival prospects and reduced or denied to those in the group with no survival prospects and to those in the group not needing special efforts for their conservation) is necessary to guide resource allocation. We argue that this decision‐making strategy is not appropriate because resources are not as limited as often assumed, and it is not evident that there are species that cannot be conserved. Small population size alone, for example, does not doom a species to extinction; plants, reptiles, birds, and mammals offer examples. Although resources dedicated to conserving all threatened species are insufficient at present, the world's economic resources are vast, and greater resources could be dedicated toward species conservation. The political framework for species conservation has improved, with initiatives such as the UN Sustainable Development Goals and other international agreements, funding mechanisms such as The Global Environment Facility, and the rise of many nongovernmental organizations with nimble, rapid‐response small grants programs. For a prioritization system to allow no extinctions, zero extinctions must be an explicit goal of the system. Extinction is not inevitable, and should not be acceptable. A goal of no human‐induced extinctions is imperative given the irreversibility of species loss.

Lower cardiac output is associated with neurodegeneration among older adults with normal cognition but not mild cognitive impairment - Elizabeth E. Moore; Dandan Liu; Corey W. Bown; Hailey A. Kresge; Deepak K. Gupta; Kimberly R. Pechman; Lisa A. Mendes; L. Taylor Davis; Katherine A. Gifford; Adam W. Anderson; Thomas J. Wang; Bennett A. Landman; et al. (Brain Imaging and Behavior, 2021)

Assessing the impact of taxon resolution on network structure - David R. Hemprich‐Bennett; Hernani F. M. Oliveira; Steven C. Le Comber; Stephen J. Rossiter; Elizabeth L. Clare (Ecology, 2021)
Constructing ecological networks has become an indispensable approach in understanding how different taxa interact. However, the methods used to generate data in network research vary widely among studies, potentially limiting our ability to compare results meaningfully. In particular, methods of classifying nodes vary in their precision, likely altering the architecture of the network studied. For example, rather than being classified as Linnaean species, taxa are regularly assigned to morphospecies in observational studies, or to molecular operational taxonomic units (MOTUs) in molecular studies, with the latter defined based on an arbitrary threshold of sequence similarity. Although the use of MOTUs in ecological networks holds great potential, especially for allowing rapid construction of large data sets of interactions, it is unclear how the choice of clustering threshold can influence the conclusions obtained. To test the impact of taxonomic precision on network architecture, we obtained and analyzed 16 data sets of ecological interactions, inferred from metabarcoding and observations. Our comparisons of networks constructed under a range of sequence thresholds for assigning taxa demonstrate that even small changes in node resolution can cause wide variation in almost all key metric values. Moreover, relative values of commonly used metrics such as robustness were seen to fluctuate continuously with node resolution, thereby potentially causing error in conclusions drawn when comparing multiple networks. In observational networks, we found that changing node resolution could, in some cases, lead to substantial changes to measurements of network topology. Overall, our findings highlight the importance of classifying nodes to the greatest precision possible, and demonstrate the need for caution when comparing networks that differ with respect to node resolution, even where taxonomic groups and interaction types are similar. In such cases, we recommend that comparisons of networks should focus on relative differences rather than absolute values between the networks studied.

Climate and local environment structure asynchrony and the stability of primary production in grasslands - Benjamin Gilbert; Andrew S. MacDougall; Taku Kadoya; Munemitsu Akasaka; Joseph R. Bennett; Eric M. Lind; Habacuc Flores‐Moreno; Jennifer Firn; Yann Hautier; Elizabeth T. Borer; Eric W. Seabloom; Peter B. Adler; et al. (Global Ecology and Biogeography, 2020)
Aim Climate variability threatens to destabilize production in many ecosystems. Asynchronous species dynamics may buffer against such variability when a decrease in performance by some species is offset by an increase in performance of others. However, high climatic variability can eliminate species through stochastic extinctions or cause similar stress responses among species that reduce buffering. Local conditions, such as soil nutrients, can also alter production stability directly or by influencing asynchrony. We test these hypotheses using a globally distributed sampling experiment. Location Grasslands in North America, Europe and Australia. Time period Annual surveys over 5 year intervals occurring between 2007 and 2014. Major taxa studied Herbaceous plants. Methods We sampled annually the per species cover and aboveground community biomass [net primary productivity (NPP)], plus soil chemical properties, in 29 grasslands. We tested how soil conditions, combined with variability in precipitation and temperature, affect species richness, asynchrony and temporal stability of primary productivity. We used bivariate relationships and structural equation modelling to examine proximate and ultimate relationships. Results Climate variability strongly predicted asynchrony, whereas NPP stability was more related to soil conditions. Species richness was structured by both climate variability and soils and, in turn, increased asynchrony. Variability in temperature and precipitation caused a unimodal asynchrony response, with asynchrony being lowest at low and high climate variability. Climate impacted stability indirectly, through its effect on asynchrony, with stability increasing at higher asynchrony owing to lower inter‐annual variability in NPP. Soil conditions had no detectable effect on asynchrony but increased stability by increasing the mean NPP, especially when soil organic matter was high. Main conclusions We found globally consistent evidence that climate modulates species asynchrony but that the direct effect on stability is low relative to local soil conditions. Nonetheless, our observed unimodal responses to variability in temperature and precipitation suggest asynchrony thresholds, beyond which there are detectable destabilizing impacts of climate on primary productivity.

Integrating team science into interdisciplinary graduate education: an exploration of the SESYNC Graduate Pursuit - Kenneth E. Wallen; Karen Filbee-Dexter; Jeremy B. Pittman; Stephen M. Posner; Steven M. Alexander; Chelsie L. Romulo; Drew E. Bennett; Elizabeth C. Clark; Stella J.M. Cousins; Bradford A. Dubik; Margaret Garcia; Heather A. Haig; et al. (Journal of Environmental Studies and Sciences, 2019)

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

Legal ivory trade in a corrupt world and its impact on African elephant populations - Elizabeth L. Bennett (Conservation Biology, 2015)
Illegal hunting of African elephants (Loxodonta africana) for ivory is causing rapid declines in their populations. Since 2007, illegal ivory trade has more than doubled. African elephants are facing the most serious conservation crisis since 1989, when international trade was banned. One solution proposed is establishment of a controlled legal trade in ivory. High prices for ivory mean that the incentives to obtain large quantities are high, but the quantity of tusks available for trade are biologically constrained. Within that context, effective management of a legal ivory trade would require robust systems to be in place to ensure that ivory from illegally killed elephants cannot be laundered into a legal market. At present, that is not feasible due to corruption among government officials charged with implementing wildlife‐related legislation. With organized criminal enterprises involved along the whole commodity chain, corruption enables the laundering of illegal ivory into legal or potentially legal markets. Poachers and traffickers can rapidly pay their way out of trouble, so the financial incentives to break the law heavily outweigh those of abiding by it. Maintaining reliable permitting systems and leak‐proof chains of custody in this context is challenging, and effective management breaks down. Once illegal ivory has entered the legal trade, it is difficult or impossible for enforcement officers to know what is legal and illegal. Addressing corruption throughout a trade network that permeates countries across the globe will take decades, if it can ever be achieved. That will be too late for wild African elephants at current rates of loss. If we are to conserve remaining wild populations, we must close all markets because, under current levels of corruption, they cannot be controlled in a way that does not provide opportunities for illegal ivory being laundered into legal markets. Comercio Legal de Marfil en un Mundo Corrupto y su Imapacto sobre Poblaciones de Elefantes

Anthropogenic‐based regional‐scale factors most consistently explain plot‐level exotic diversity in grasslands - Andrew S. MacDougall; Joseph R. Bennett; Jennifer Firn; Eric W. Seabloom; Elizabeth T. Borer; Eric M. Lind; John L. Orrock; W. Stanley Harpole; Yann Hautier; Peter B. Adler; Elsa Cleland; Kendi Davies; et al. (Global Ecology and Biogeography, 2014)
Aim Evidence linking the accumulation of exotic species to the suppression of native diversity is equivocal, often relying on data from studies that have used different methods. Plot‐level studies often attribute inverse relationships between native and exotic diversity to competition, but regional abiotic filters, including anthropogenic influences, can produce similar patterns. We seek to test these alternatives using identical scale‐dependent sampling protocols in multiple grasslands on two continents. Location Thirty‐two grassland sites in N orth A merica and A ustralia. Methods We use multiscale observational data, collected identically in grain and extent at each site, to test the association of local and regional factors with the plot‐level richness and abundance of native and exotic plants. Sites captured environmental and anthropogenic gradients including land‐use intensity, human population density, light and soil resources, climate and elevation. Site selection occurred independently of exotic diversity, meaning that the numbers of exotic species varied randomly thereby reducing potential biases if only highly invaded sites were chosen. Results Regional factors associated directly or indirectly with human activity had the strongest associations with plot‐level diversity. These regional drivers had divergent effects: urban‐based economic activity was associated with high exotic : native diversity ratios; climate‐ and landscape‐based indicators of lower human population density were associated with low exotic : native ratios. Negative correlations between plot‐level native and exotic diversity, a potential signature of competitive interactions, were not prevalent; this result did not change along gradients of productivity or heterogeneity. Main conclusion We show that plot‐level diversity of native and exotic plants are more consistently associated with regional‐scale factors relating to urbanization and climate suitability than measures indicative of competition. These findings clarify the long‐standing difficulty in resolving drivers of exotic diversity using single‐factor mechanisms, suggesting that multiple interacting anthropogenic‐based processes best explain the accumulation of exotic diversity in modern landscapes.

Wildlife trade products available to U.S. military personnel serving abroad - Heidi E. Kretser; McKenzie F. Johnson; Lisa M. Hickey; Peter Zahler; Elizabeth L. Bennett (Biodiversity and Conservation, 2012)

The World Can't Have Wild Tigers and Eat Them, Too - BRIAN GRATWICKE; ELIZABETH L. BENNETT; STEVEN BROAD; SARAH CHRISTIE; ADAM DUTTON; GRACE GABRIEL; CRAIG KIRKPATRICK; KRISTIN NOWELL (Conservation Biology, 2008)

Hunting for Consensus: Reconciling Bushmeat Harvest, Conservation, and Development Policy in West and Central Africa - ELIZABETH L. BENNETT; ERIC BLENCOWE; KATRINA BRANDON; DAVID BROWN; ROBERT W. BURN; GUY COWLISHAW; GLYN DAVIES; HOLLY DUBLIN; JULIA E. FA; E. J. MILNER‐GULLAND; JOHN G. ROBINSON; J. MARCUS ROWCLIFFE; et al. (Conservation Biology, 2007)

Is There a Link between Wild Meat and Food Security? - Elizabeth L. Bennett (Conservation Biology, 2002)

Timber Certification: Where Is the Voice of the Biologist? - Elizabeth L. Bennett (Conservation Biology, 2001)
Editor's note: This Conservation Forum begins with a reprinted editorial by Elizabeth Bennett from the August 2000 issue of Conservation Biology . Several papers were submitted in repsonse to that piece, and it is reprinted here to start this forum.

The Joint Effort of Timber Certification - Elizabeth L. Bennett (Conservation Biology, 2001)

Timber Certification: Where Is the Voice of the Biologist? - Elizabeth L. Bennett (Conservation Biology, 2000)

The value of a mangrove area in Sarawak - Elizabeth L. Bennett; Colin J. Reynolds (Biodiversity and Conservation, 1993)